Find the derivative of y=e^(2x)*(x^2-4x-2).

Notice that y can be expressed as y=f(x)g(x), in which f(x)=e^(2x) and g(x)=x^2-4x-2.Through the product rule, we know that dy/dx=f'(x)g(x)+f(x)g'(x).Through the chain rule, we can solve f(x) by rewriting in the form f=e^u, u=2xf'(x)=df/du * du/dxf('x)=e^u * 2f'(x)=2e^(2x)We solve g(x) by simply differentiating a polynomial function with degree 2, i.e. given the term ax^b we replace it with abx^(b-1)g'(x)=2x-4Therefore, dy/dx = 2e^(2x)(x^2-4x-2) + e^(2x)*(2x-4).

Answered by Samuel H. Maths tutor

7839 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Given that (2x-1) : (x-4) = (16x+1) : (2x-1), find the possible values of x


Find the x value of the stationary points of the graph y = x^2e^x


How do you find (and simplify) an expression, in terms of n, for the sum of the first n terms of the series 5 + 8 + 11 + 14 + ... ?


Calculate the distance of the centre of mass from AB and ALIH of the uniform lamina.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences